Tarsal Navicular Bone Stress Injuries: A Multicenter Case Series Investigating Clinical Presentation, Diagnostic Approach, Treatment, and Return to Sport in Adolescent Athletes - Mehta, S.; Zheng, E.; Heyworth, B. E.; Rizzone, K.; Halstead, M.; Brown, N.; Stinson, Z.; Nussbaum, E. D.; Gray, A.; Segovia, N.; Kraus, E. (The American Journal of Sports Medicine, 2023)
Background: Tarsal navicular bone stress injuries (BSIs) are considered "high risk" because of prolonged healing times and higher rates of nonunion in adult populations but, to our knowledge, have not been comprehensively examined in adolescent athletes.